TURIZM SOHASIDA KADRLAR YETISHMOVCHILIGI MUAMMOSI - To'lqunov Azizbek Utkir o'g'li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article analyzes the problem of personnel shortage in the tourism sector in Uzbekistan. As a research methodology, literature analysis, statistical data analysis and expert interviews were conducted. The results show that there are factors such as lack of qualified personnel in the tourism sector, deficiencies in the education system and low oburósi of the sector. To solve the problem, it is necessary to improve the educational system, improve personnel skills, improve working conditions and receive state support. Recommendations can become the basis for the development of personnel policy in the future.